Data Pribadi Nasabah Pada Penyedia Jasa Pinjaman Online - Manggala, Ferdiansyah Putra (Legal Spirit, 2024)
The emergence of various fintech-based companies in the increasingly widespread field of online lending and borrowing has brought several new legal problems, namely the large number of personal data belonging to user customers appearing on various sites or illegal online loan applications, so that collection actions are carried out in an intimidating manner. Issues taken regarding the form of legal protection for customers' personal data in online loans, what forms of responsibility of online loan service providers in the event of leakage and misuse of personal data against customers, and future arrangements regarding the protection of personal data for customers entering into online loan agreements. This research uses a normative juridical research type using a statutory approach, a comparative approach, and a conceptual approach. The form of legal protection is in accordance with M. Isnaeni's view, namely through internal protection where protection is realized through agreement clauses in accordance with Article 26 POJK 77/2016, and external protection emphasizes the protection provided by the government through the ratification of the UUPDP. The responsibilities of online loan providers have been regulate in Article 37 POJK 77/2016, for errors or omissions that are the responsibility of the organizer, forms of accountability in the form of compensation, compensation, and criminal provisions. As well as future arrangements regarding the protection of personal data, the existence of the UUPDP has not been able to reach public protection because there are no implementing regulations that further regulate technical implementing regulations regarding personal data protection practices.